The Effect of Fucoidan on Cellular Oxidative Stress and the CatD-Bax Signaling Axis in MN9D Cells Damaged by 1-Methyl-4-Phenypyridinium - Liang, Zhigang; Liu, Zhuli; Sun, Xuwen; Tao, Manli; Xiao, Xiao; Yu, Guoping; Wang, Xiaomin (Frontiers in Aging Neuroscience, 2019)
Background: The purpose of this study was to investigate the impact of fucoidan (FUC) on the oxidative stress response and lysosomal apoptotic pathways in the Parkinson disease（PD）cell model. Methods: The Dopaminergic nerve precursor cell line（MN9D） cells that served as a PD model in this study underwent damage induced by 100μM 1-methyl-4-phenyl pyridine (MPP+). Cell viability was assessed after FUC treatment and intracellular SOD GSH was measured via immunofluorescence assay. Cellular changes in cathepsin D, Autophagy marker Light Chain 3-II （LC3-II）, and apoptotic protein Bax were assessed by Western blot. The expression of Cat D, LC3-II, and B cell lymphoma-2-associated x protein (Bax) was also measured after addition of the cathepsin inhibitor, pepstatin A. Results: The results indicated that MN9D cell viability decreased by 50% within 24 h after 100 μM MPP+ induced toxicity. Pretreatment with 100μM Fucoidan reduced cellular expression of LC3-II and CatD in 3h and suppressed the induction of Bax protein. After pepstatin A treatment, Bax expression was significantly downregulated, which suggested that Cathepsin D may positively regulate the expression of Bax. FUC reversed the reduction of superoxide dismutase (SOD) L-Glutathione(GSH), decreased cell viability, and apoptosis induced by MPP+ in 6h, suggesting that Fucoidan can attenuate damage to MN9D cells induced by MPP+. Conclusions: Fucoidan protected lysosomes, reduced the expression of LC3-II, inhibited the expression of CatD-Bax and the oxidative stress response, suppressed apoptosis, and thus conferred protective effects for dopaminergic neural cells. Fucoidan has potential to be a next generation neuroprotective drug.